Pemanfaatan Limbah Sampah Rumah Tangga Untuk Mengurangi Pencemaran Lingkungan di Permukiman - Gusmarti, Daista; Oktavia, Della; Walid, Ahmad (TIN: Terapan Informatika Nusantara, 2020)
Until now, waste is still a serious problem in Indonesia. The behavior and habits of the community or individuals to manage waste have not led to positive behavior such as disposing of garbage in its place. With this bad habit, it is necessary to have a way to deal with household waste. Because if not handled seriously it will affect environmental health. What can be done in overcoming this problem is waste management carried out from the household and to make the community independent in solving environmental health problems. Therefore, through community empowerment efforts in solving waste problems, it is hoped that the waste problem will not only be the responsibility of the government, but also the responsibility of all levels of society. Managing waste can be done with the principle of reduce, reuse and recycle or reduce, reuse and recycle waste